Alcohol misuse in patients with alcohol‐related liver disease: How can we do better? A narrative review of the literature. (8th July 2022) - Horrell, Jane; Callaghan, Lynne; Dhanda, Ashwin
Abstract: Background: Ongoing alcohol use is strongly associated with progressive liver damage and higher mortality in patients with alcohol‐related liver disease (ArLD). Reduction in alcohol use is therefore the cornerstone of treatment to improve the long‐term outcome of these patients. However, a large proportion of patients continue to use alcohol and do not access or engage with alcohol treatment services after a diagnosis of ArLD. We reviewed the literature on factors associated with ongoing alcohol consumption among patients with ArLD to identify barriers or facilitators to their accessing alcohol treatment. Methods: A search of MEDLINE and EMBASE was conducted using search strategies relating to ArLD and the psychosocial factors hypothesized to influence alcohol reduction and/or abstinence. Results: There were few relevant studies pertinent to this population group. Several studies reported a high prevalence of mental health diagnoses associated with the severity of alcohol dependence. Social and environmental factors were shown to be important determinants of alcohol use. Common themes perceived as barriers to treatment from qualitative interviews with ArLD patients across studies included poor communication between the clinical team and patient, lack of symptoms recognized by patients themselves, and perceived loss of control over their condition. Conclusions: We recommend that future clinical studies of patient cohorts with ArLD include detailed psychosocial assessments to capture information on mental health and social factors. Qualitative studies are required to explore the patient journey pre and post hospital admission, which should focus on identifying facilitators and barriers to accessing treatment. Well‐designed, controlled studies are needed to identify patient, social, and environmental factors associated with relapse to alcohol use after a diagnosis of ArLD. These data will enable us to adapt our support for patients to enhance engagement with services and improve long‐term outcomes. Abstract : Many patients with alcohol‐related liver disease do not engage with alcohol services and have poor outcomes. Our literature review found that social isolation, unemployment and mental health diagnoses were associated with ongoing alcohol use. A poor understanding of their health, a lack of physical symptoms and perceived loss of control over their health were identified as barriers to alcohol treatment. Future studies should explore facilitators and barriers to accessing treatment to enable co‐design of effective alcohol services with key stakeholders.